A holistic based digital forensic readiness framework for Zenith Bank, Nigeria - Garba, Adamu Abdullahi (2015)
The advancement of internet has made many business organizations conduct their operation automatically, in effect its open a possibly dangerous unforeseen information security incidents of both illegal and civil nature. Therefore, if any organization does’t arrange themselves for such instances, it’s likely that vital significant digital evidence will be damage. In other word an organization should has a digital forensic readiness framework (DFR). DFR is the capacity of anyassociation to exploit its prospective to use digital evidence whilst minimizing the cost of investigation. Subsequently, in order to prepare organizations for incident responds, the application of digital forensic readiness policies and procedures is important. Contemporary lack of forensic skills is one of the factors that make organizations reluctant to implement digital forensics. This project propose a holistic-based framework of DFR and investigate how it can be applied to Zenith Bank Plc. This paper surveys existing frameworks to identify the best-suited practical components for Zenith Bank’s operational unit.